2018
DOI: 10.1542/peds.2017-2432
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Outcomes and Resource Use After Hospitalization for Cardiac Surgery by Neighborhood Income

Abstract: Children from lower-income neighborhoods are at increased risk of mortality and use more resource intensive care than children from higher-income communities, even after accounting for disparities between races, payers, and centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 22 publications
(12 reference statements)
2
67
1
Order By: Relevance
“…The following types of mortality were analysed: in‐hospital (n = 10), infant (<1 year, n = 6), neonatal (<28 days, n = 2), postoperative (n = 2), post‐discharge (n = 3), intra‐stage (n = 2), and long‐term (>1 year, n = 6) (see Table for study‐specific definitions). Four measures of SES were reported in the included studies: area‐based poverty (n = 13), parental (maternal or paternal) or area‐based education (n = 9), individual health insurance status (n = 8), and area‐based income (n = 8) . The definitions for SES measures used in individual studies are given in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following types of mortality were analysed: in‐hospital (n = 10), infant (<1 year, n = 6), neonatal (<28 days, n = 2), postoperative (n = 2), post‐discharge (n = 3), intra‐stage (n = 2), and long‐term (>1 year, n = 6) (see Table for study‐specific definitions). Four measures of SES were reported in the included studies: area‐based poverty (n = 13), parental (maternal or paternal) or area‐based education (n = 9), individual health insurance status (n = 8), and area‐based income (n = 8) . The definitions for SES measures used in individual studies are given in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The definitions for SES measures used in individual studies are given in Table . The included articles were based on US (n = 22), UK (n = 5), and Panama (n = 1) populations. Most articles included all CHD subtypes combined (n = 21), with the rest including cases of HLH or single ventricle (SV) defects (n = 5), atrioventricular septal defect (AVSD, n = 1), and a composite group of “critical” subtypes (n = 1) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A particularly novel finding in the present study was the association of decreased household income with worse inhospital survival after OHT. Andersen et al showed that children from lower‐income neighborhoods have worse mortality and higher resource utilization, including LOS and hospital costs, after cardiac surgery. Similarly, Kucik et al demonstrated an increased mortality in infants with CHD from socioeconomically disadvantaged communities.…”
Section: Discussionmentioning
confidence: 99%